Graywater reuse guidance and demonstration using a constructed wetland treatment system - Bergdolt, Jesse Hawk, author; Sharvelle, Sybil E., advisor; Roesner, Larry A., advisor; Glick, Scott, committee member (Colorado State University. Libraries, 2011)
Communities throughout the United States and abroad are developing interest in innovative approaches to sustaining their freshwater resources. One method, graywater reuse for non-potable demands, is gaining popularity because it allows the reuse of minimally contaminated wash water generated at the home/office for non-potable demands, which then reduces the demand for treated water and preserves source waters. Graywater is defined as any wastewater generated at the home or office excluding water from the toilets, kitchen sinks, and dishwasher, but includes wastewater from the laundry, shower, and bathroom sinks. When compared to other wastewater generated in the home graywater is minimally contaminated with lower concentrations of organics, solids, nutrients, and pathogens, thereby rendering the water suitable for reuse with minimal treatment when compared to other domestic wastewater sources. Despite widespread interest in this innovative approach information on the separation and design of residential and/or commercial scale graywater systems have been limited. The objective of this study was 1) to provide a graywater reuse manual for home or business owners interested in separating sources of graywater from blackwater for graywater reuse and 2) to determine the first order removal rates (k) of graywater constituents using both a free water surface (FWS) and subsurface flow (SF) constructed wetlands, in order to provide design guidance for future constructed wetlands that will be used to treat graywater. Information regarding the separation and reuse of graywater is important to the success of graywater reuse systems. This thesis provides information to business and home owners about the separation of graywater from blackwater for graywater reuse. Part one of this thesis outlines the methods and equipment needed to install a dual plumbing system for the purpose of graywater reuse. Part one also describes how to design an individual graywater reuse system specific to the needs of the home or business owners, the technologies and equipment necessary for graywater reuse systems, known maintenance requirements for graywater systems, and best management practices to ensure safe reuse of graywater. Individual graywater reuse systems for the home or office are too small to treat large amounts of graywater produced by residential neighborhoods or communities. Consideration should be given to treatment options that can handle and treat a large amount of graywater. Constructed wetlands can offer a scalable, economically sound, low tech and easily maintained method of treating graywater for large scale irrigation reuse. While constructed wetlands are an appropriate technology for graywater treatment there is little research providing the removal rates for the design of constructed wetlands for graywater reuse. Determining removal rates is important for creating wetland design standards for graywater treatment and reuse. Part two of this thesis provides the experimental results for determining the seasonal flow adjusted removal rates (k) of graywater constituents using a free water surface (FWS) constructed wetland and a subsurface flow (SF) constructed wetland. Removal rates were evaluated over a two year period (2008-2010) for a FWS wetland and evaluated over the summer/fall of 2010 for a SF wetland. The results for the FWS included the biochemical oxygen demand (BOD5) removal rates of 15.9 (m yr-1) for summer removal, 15.2(m yr-1) for fall removal, and 5.6 (m yr-1) for winter/spring removal. The total nitrogen (TN) removal rates were 16.4 (m yr-1) for summer removal, 8.5 (m yr-1) for fall removal, and 5.5 (m yr-1) for winter removal. The total organic carbon (TOC) removal rates were 10.4 (m yr-1) for summer removal and inconclusive for the TOC removal in the fall and winter seasons. The results for the SF during the summer included a BOD5 removal rate of 19.1 (m yr-1), a TOC removal of 22.8 (m yr-1), a TN removal rate of 21.3 (m yr-1), and an ammonia removal rate of 32.6 (m yr-1). The results were inconclusive for the fall season due to a limited amount of data. When compared to other literature k values for sizing wetland for agricultural and municipal wastewater, results from this study had lower k values for BOD, which resulted in a larger required surface area (SA) for wetland design. The TN and ammonia k values were comparable to other literature design values.
Keywords: reuse; constructed wetland; graywater; dual separation